Proteomics of the dentate gyrus reveals semantic dementia specific molecular pathology - Merel O. Mol; Suzanne S. M. Miedema; Shamiram Melhem; Ka Wan Li; Frank Koopmans; Harro Seelaar; Kurt Gottmann; Volkmar Lessmann; Netherlands Brain Bank; August B. Smit; John C. van Swieten; Jeroen G. J. van Rooij (Acta Neuropathologica Communications, 2022)
Abstract Semantic dementia (SD) is a clinical subtype of frontotemporal dementia consistent with the neuropathological diagnosis frontotemporal lobar degeneration (FTLD) TDP type C, with characteristic round TDP-43 protein inclusions in the dentate gyrus. Despite this striking clinicopathological concordance, the pathogenic mechanisms are largely unexplained forestalling the development of targeted therapeutics. To address this, we carried out laser capture microdissection of the dentate gyrus of 15 SD patients and 17 non-demented controls, and assessed relative protein abundance changes by label-free quantitative mass spectrometry. To identify SD specific proteins, we compared our results to eight other FTLD and Alzheimer’s disease (AD) proteomic datasets of cortical brain tissue, parallel with functional enrichment analyses and protein–protein interactions (PPI). Of the total 5,354 quantified proteins, 151 showed differential abundance in SD patients (adjusted P-value < 0.01). Seventy-nine proteins were considered potentially SD specific as these were not detected, or demonstrated insignificant or opposite change in FTLD/AD. Functional enrichment indicated an overrepresentation of pathways related to the immune response, metabolic processes, and cell-junction assembly. PPI analysis highlighted a cluster of interacting proteins associated with adherens junction and cadherin binding, the cadherin-catenin complex. Multiple proteins in this complex showed significant upregulation in SD, including β-catenin (CTNNB1), γ-catenin (JUP), and N-cadherin (CDH2), which were not observed in other neurodegenerative proteomic studies, and hence may resemble SD specific involvement. A trend of upregulation of all three proteins was observed by immunoblotting of whole hippocampus tissue, albeit only significant for N-cadherin. In summary, we discovered a specific increase of cell adhesion proteins in SD constituting the cadherin-catenin complex at the synaptic membrane, essential for synaptic signaling. Although further investigation and validation are warranted, we anticipate that these findings will help unravel the disease processes underlying SD.